2018
DOI: 10.1007/s13239-018-0363-0
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Matrix Stiffness and ß-Catenin Signaling in Endothelial-to-Mesenchymal Transition of Aortic Valve Endothelial Cells

Abstract: Valve stiffening is a hallmark of aortic valve stenosis caused by excess extracellular matrix accumulation by myofibroblasts. We aimed to elucidate whether matrix stiffness regulates endothelial-to-mesenchymal transition (EndMT) of adult valvular endothelial cells (VECs) to myofibroblasts as a mechanism to further promote valve fibrosis. In addition, we specifically examined the role of the Wnt/β-catenin signaling pathway in the development of myofibroblasts during EndMT, as Wnt/β-catenin signaling has been im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 30 publications
5
46
0
Order By: Relevance
“…In summary, these results validate the proposed cell identities and confirm their differentiation trajectories, demonstrating that endothelial cells are able to undergo EHT and endothelial-to-mesenchymal transition (EndoMT) (27, 28, 29, 30, 31) to generate haematopoietic and mesenchymal populations, respectively. Additionally, we identified a sorting strategy to enrich for HPCs generated in vitro and confirmed their multilineage haematopoietic potential using differentiation assays.…”
Section: Resultssupporting
confidence: 78%
“…In summary, these results validate the proposed cell identities and confirm their differentiation trajectories, demonstrating that endothelial cells are able to undergo EHT and endothelial-to-mesenchymal transition (EndoMT) (27, 28, 29, 30, 31) to generate haematopoietic and mesenchymal populations, respectively. Additionally, we identified a sorting strategy to enrich for HPCs generated in vitro and confirmed their multilineage haematopoietic potential using differentiation assays.…”
Section: Resultssupporting
confidence: 78%
“…β-catenin signaling has been involved in epithelial-to-mesenchymal transition in pulmonary disease and cancer [8,12,26]. Also, β-catenin has been reported to promote EndMT through nuclear accumulation and subsequent activation of TCF/Lef transcription factors [13, 14]. In the current study, we revealed that overexpression of FAM13A decelerates the EndMT process in association with reduced active β-catenin levels and its nuclear accumulation in endothelial cells.…”
Section: Discussionsupporting
confidence: 55%
“…β-catenin is crucially involved in the epithelial-mesenchymal transition that play an important role in the pathogenesis of cancer [12] and pulmonary fibrosis. Also, there are many reports describing the role of β-catenin in EndMT that is implicated in the vascular remodeling for pulmonary hypertension [1315]. These findings urged us to investigate a potential role of FAM13A in the pathogenesis of pulmonary hypertension, and we here identified a protective role of FAM13A in the development of pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 53%
“…β-catenin signaling has been involved in epithelial-to-mesenchymal transition in pulmonary disease and cancer [8,12,26]. Also, β-catenin has been reported to promote EndMT through nuclear accumulation and subsequent activation of TCF/Lef transcription factors [13,14]. In the current study, we revealed that overexpression of FAM13A decelerates the (n = 3 each).…”
Section: Discussionsupporting
confidence: 53%
“…β-catenin is crucially involved in the epithelial-mesenchymal transition that plays an important role in the pathogenesis of cancer [12] and pulmonary fibrosis. Also, there are many reports describing the role of β-catenin in EndMT that is implicated in the vascular remodeling for pulmonary hypertension [13][14][15]. These findings urged us to investigate a potential role of FAM13A in the pathogenesis of pulmonary hypertension, and we here identify a protective role of FAM13A in the development of pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 70%